IMPLEMENTASI LESSON STUDY DALAM MATA KULIAH ANALISIS KESALAHAN BERBAHASA UNTUK MENINGKATKAN KEMAMPUAN KOOPERATIF MAHASISWA SEMESTER VII STKIP MUHAMMADIYAH KOTABUMI - Dewi Ratnaningsih (Edukasi Lingua Sastra, 2018)
This article talks about The Implementation of Lesson Study on "Analisis Kesalahan Berbahasa" (Language Error Analysis) subject. The purpose of this research is to describe the implementation of lesson study and to see the effect of increasing cooperative skill of student. Based on the observation, the are some lesson learnt: a) the use of collaborative learning method could give space to student to make discussion, so it could increase student cooperative skill, b) there are intensive discussion on the partial group (consist of 2—4 members. It shows that implementation of lesson study could increase student cooperative.